Necrotizing periodontal disease in a nutritionally deficient patient: A case report - Sally Sheng; Haemin H. Kim; Hsiu-Wan Meng; Gena D. Tribble; Jennifer Chang (Frontiers Media S.A., 2022)
Necrotizing periodontal disease (NPD) is a microbial infectious inflammatory disease of the gingiva and/or periodontium that is characterized by a rapid onset of inflammation, pain, and "punched out" cratered interdental papillae. Although NPD is not very common, diagnosis is mostly based on its unique clinical presentation. Some predisposing factors for developing NPD include poor oral hygiene, smoking, malnutrition, immunosuppression (such as in HIV infection, uncontrolled diabetes, and cancer), and stress. This report presents the case of a 22-year-old Caucasian woman, who was a heavy smoker but with otherwise showed no systemic disease and who suffered from severe inflammation of the gingiva, ulceration, and necrosis of the interdental papillae, and pseudomembrane formation. The patient had been hospitalized for a seizure episode and was diagnosed with malnutrition-induced seizure. NPD was diagnosed and the patient was treated successfully with nonsurgical scaling and root planing and behavioral modifications including smoking cessation and balanced nutrition intake. Disease remission was achieved after treatment. In addition, this case report reviews the effect of nutrients on the health of the periodontium.